Energy Sector Performance and Real Sector Activity in Nigeria - Agu, Sunday Virtus; Azike, Lawrence Chike; Kalu, U. Chris (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
In spite of the remarkable achievements in the Nigerian economy, the supply of electricity has remained the poor same and this has led to a shift in other alternative sources of power which require burning of fossil fuels and has consequently increased toxic emission. This paper examined the relationship between energy sector performance and real sector activity in Nigeria between 1986 to 2021 using the dynamic autoregressive distributed lag and Granger causality approaches. The model included variables are manufacturing value added (the dependent variable) and electricity consumption, the real gross domestic product, foreign direct investment, population growth and private sector credit as explanatory variables. The finding showed that electricity consumption (performance) has a positive but insignificant impact on manufacturing value added (productivity), while both foreign direct investment and real gross domestic product have positive and significant impacts on manufacturing value added. Furthermore, the Granger causality result showed bidirectional causality between electricity consumption and manufacturing value added and unidirectional causality between manufacturing value added and private sector credit. This paper recommended among others the need for monetary and fiscal policy interactions promote real sector- manufacturing productivity, thus, the Central Bank of Nigeria and Bank of Industry can provide credit incentives at lower cost for industrialist and manufacturers.